Phenotypic and genotypic characterisation of Blastocystis hominis isolates implicates subtype 3 as a subtype with pathogenic potential - Tan, T.C.; Suresh, K.G.; Smith, H.V. (2008)
Despite frequent reports on the presence of Blastocystis hominis in human intestinal tract, its pathogenicity remains a matter of intense debate. These discrepancies may be due to the varying pathogenic potential or virulence of the isolates studied. The present study represents the first to investigate both phenotypic and genotypic characteristics of B. hominis obtained from symptomatic and asymptomatic individuals. Symptomatic isolates had a significantly greater size range and lower growth rate in Jones' medium than asymptomatic isolates. The parasite cells of symptomatic isolates exhibited rougher surface topography and greater binding affinity to Canavalia ensiformis (ConA) and Helix pomatia (HPA). The present study also identifies further phenotypic characteristics, which aided in differentiating the pathogenic forms from the non-pathogenic forms of B. hominis. Blastocystis subtype 3 was found to be correlated well with the disease.